2019
DOI: 10.3390/ma12193177
|View full text |Cite
|
Sign up to set email alerts
|

Elemental Silver Nanoparticles: Biosynthesis and Bio Applications

Abstract: The data on the specifics of synthesis of elemental silver nanoparticles (Ag-NP) having various geometric shapes (pseudo spherical, prismatic, cubic, trigonal-pyramidal, etc.), obtained by using various biological methods, and their use in biology and medicine have been systematized and generalized. The review covers mainly publications published in the current 21st century. Bibliography: 262 references.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
33
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 237 publications
(467 reference statements)
0
33
0
1
Order By: Relevance
“…8,9 Additionally, these nanoparticles have turned out to be essential for their excellent chemical and thermal stability. 10 ZnO NPs have remarkable fluorescence in cells so that they are biomarkers in relevant clinical and biomedical applications. 11 They have emerged as a promising and innovative technique for the efficient delivery of drugs in treating some diseases by specific targeting.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…8,9 Additionally, these nanoparticles have turned out to be essential for their excellent chemical and thermal stability. 10 ZnO NPs have remarkable fluorescence in cells so that they are biomarkers in relevant clinical and biomedical applications. 11 They have emerged as a promising and innovative technique for the efficient delivery of drugs in treating some diseases by specific targeting.…”
Section: Introductionmentioning
confidence: 99%
“… 8 , 9 Additionally, these nanoparticles have turned out to be essential for their excellent chemical and thermal stability. 10 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several noble nanomaterials such as silver, gold, mercury, platinum, copper and zinc are employed in the biological, agricultural and biomedical fields (Arvizo et al 2012; Johnson alias Antonysamy et al, 2017). Ag NPs have been well-known in manmade activities since ancient time (Mikhailov et al, 2019). The crystalline nature and morphology of NPs play pivotal role in the parameter of their chemical and physical traits (Coe et al, 2002;Mittal et al, 2016;Rizwan et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…It was also demonstrated that a much greater variety of nanoparticle assemblies could be produced by cells along the "bottom-up" approach (Zhang et al, 2011;Woehl et al, 2014;Sánchez-López et al, 2020) (Figure 1). Observations clearly show that nanocrystals can nucleate from an aqueous solution via a threestep mechanism: spinodal decomposition, clusterization, and nanocrystallization (Luo et al, 2017;Tan et al, 2017;Xie et al, 2017;Liao et al, 2019;Mikhailov and Mikhailova, 2019;Wang et al, 2019). The amorphous clusters of zero-valent atoms (up to 1-2 nm) are direct precursors of the bigger crystalline nanoparticles (Malis et al, 2011;Wan et al, 2013;Loh et al, 2017;Singh et al, 2020).…”
Section: Introductionmentioning
confidence: 99%